Electrospray tandem mass spectrometric measurements of organotin compounds. Issue 1 (2004) - Banoub Banoub, Joseph H. Joseph H.; Miller-Banoub Miller-Banoub, Judith Judith; Sheppard Sheppard, George V. George V.; Hodder Hodder, Howard J. Howard J.
Abstract : Electrospray mass spectrometry of a series of organotin compounds in solutions of methanol are reported. Low energy collision‒induced dissociation MS/MS analysis of diagnostic precursor ions confirmed the characteristic fingerprint patterns obtained in the conventional electrospray spectra and proved to be a specific and very sensitive method for quantification of the (R3 Sn)2 O and the series of Rn SnX4–n compounds in environmental matrices. Concentrations of butyltin compounds (TBTX, DBTX2 and MBTX3 ) in sediment reference materials PACS-1 and PACS-2 and butyltin and phenyltin compounds (TBTX, DBTX2, MBTX3, TPTX, DPTX2 and DPTX3 ) in Quasimeme II biota reference material (QSP001BT) were determined. The organotin compounds were extracted from the reference materials with 1-butanol followed by dilution with methanol containing 1 mM ammonium acetate. The extracts were introduced directly into the electrospray source by a continuous flow of MeOH : H2 O (60 :40). Quantitation of TBTX, DBTX2, TPTX, DPTX2 and DPTX3 was achieved by low energy CID tandem mass spectrometry using the Multiple Reaction Monitoring (MRM) analysis with the appropriate MS/MS transitions (positive ion electrospray ionization). Quantitation of MBTX3 was achieved using a negative ion electrospray CID tandem mass spectrometry method. For all samples quantitation was achieved by use of the method of standard addition, relative extraction recoveries were determined spiking with internal standards of mono‒, di‒ and triorganotin compounds separately to different samples.